DEVELOPMENT OF THE COMPETENCE OF CIVIL SERVANTS TO WORK WITH CITIZENS IN A DISSATISFIED MOOD (American Journal of Interdisciplinary Research and Development, 2023)
One of the priorities of each state policy is the effectiveness of the activities of civil servants, in particular, the development of competencies of civil servants is the basis of the reforms carried out by the country. After all, the fact that civil servants do not have enough competence can cause a mood of discontent among citizens. This article presents a theoretical analysis of the competence of civil servants to work with citizens in a dissatisfied mood, an analysis of foreign experience on the main competencies in the training of civil servants, a theoretical analysis of the content of the mood of discontent among the population, the analysis of reforms carried out in Uzbekistan in the approval of citizens.